Pengembangan dan Penerapan Aplikasi Absensi Berbasis Web Menggunakan Koneksi Wi-Fi untuk Meningkatkan Akurasi Data Kehadiran di CNT Car Wash - Riswinda Azzahra, Zavira; Ghoyali, Sarifudin; Rom Adonie, Lulu; Haryono, Wasis (Green Publisher Indonesia, 2024)
The paper-based manual attendance system used today causes various problems, such as low data accuracy, manipulation of attendance time, slow data processing process, and wasteful use of resources. By switching to a web-based digital attendance system, companies can improve accuracy, efficiency, and transparency in employee attendance management. The use of this system can also reduce data input errors, speed up report processing, reduce paper use, and increase overall productivity. The application of this technology is in line with the development of digitalization that is increasingly needed by modern companies. The research methods used in this practical work report include interviews, observations, literature studies, and application development methods using the waterfall model. Through interviews with related parties, direct observation, and data support from relevant literature, the author developed a web-based digital attendance application with a systematic and sequential approach according to the waterfall method. This study results in the conclusion that the implementation of a web-based attendance system in CNT Car Wash not only increases operational productivity, but also prepares companies to compete in the digital era. By continuing to innovate and utilize technology, CNT Car Wash can optimize human resource management, provide the best service to customers, and support business sustainability in the long term.